The Impact of International Portfolio Flows on Exchange Rate Volatility in Emerging Markets in Asia - Shasazuhni, Mohamad; Wibowo, Buddi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research explores how inflows of stock and bond portfolios impact the level of volatility in exchange rates, using monthly data from the United States vis a vis seven emerging Asia countries (China Mainland, China Taiwan, The Philippines, India, Indonesia, Malaysia, and Thailand) between 2010 and 2022. The study uses statistical models such as Ordinary Least Square (OLS), Generalized Autoregressive Conditional Heteroscedasticity (GARCH), and Threshold Generalized Autoregressive Conditional Heteroscedasticity (TGARCH). The findings indicate that net stock and net bond flows have a significant impact on exchange rates volatility, and net stock flows have a more significant impact on exchange rates volatility rather than net bond flows..